Sifat Fisikokimia dan Total Mikroba Telur Itik Asin Hasil Teknik Penggaraman dan Lama Penyimpanan yang Berbeda - Z Wulandari (Faculty of Animal Science, Bogor Agricultural University, 2004)
This research was aimed to study physicochemical properties and total plate count of salted duck egg produced by pressure method during storage. This research consisted of two stages. First stage was producing salted duck egg based on the most optimal result that was by soaking the egg into salted water with comparison between salt and water = 1: 4. The soaking process was carried out in pressure machine for 10 days with pressure force 4.8 atm. As control, the egg was soaked in the salted water with same concentration for 10 days without pressure. In the second stage, the two samples were stored in the room temperature for 4 weeks. The analysis of experimental variables was carried out once a week. The experimental variables were: weight loss, albumen and yolk pH, water content of albumen and yolk, ash content of albumen and yolk, NaCl content of albumen and yolk, and total plate count. Completely Block Randomized Design with factorial pattern 2 x 5 was used in this experiment. The first factor was soaking treatment with pressure and without pressure and the second factor was storage time (0 week, 1 week, 2 weeks, 3 weeks, and 4 weeks). Three replication of this research was treated as block. Analysis of variance and Duncan's multiple range test were used to analyze data. This result showed that physicochemical properties of salted duck eggs soaked with pressure during storage was giving the best result than those soaked without pressure. Whereas total plate count of salted duck eggs soaked with pressure during storage was higher than those soaked without pressure. Key words: salted egg, pressure, physicochemical